DESÁGUA UMA POROROCA NO CORDÃO DE PÁSSARO: o processo de criação de um corpo-pororoca no pássaro junino tangará - PACHECO, Thaiana Caroline Falcão (2022)
This work aims to unveil the creation process of the character Pororoca, played by me, while playing in Cordão de Anjo Junino Tangara, an experimental theater group from Mosqueiro-PA that works with Teatro Popular, more specifically with Céu Junino. Namely, Bird Junino (Moura, 1997) is a cultural manifestation of the Amazon region that consists of a cabocla operetta. To this end, I use aspects of an autoetnographic approach to dance, which describes the challenges of composition for the scene, as well as other aspects that involve the socio-political and cultural context of the Cordões de Selvagem, in addition to dialoguing with some important authors in the search for concepts that contributed to the process in question, such as Loureiro (2001), Moura (1997) and Maués (1997) who, in their research, study the cultural manifestation of the June bird as a constituent of paraense Amazonian culture, Fabião (2010) , who in his studies presents an understanding of a scenic body that opposes the fiction x reality dichotomy by not dissociating scenic body from everyday body, Ferracini (1998), Vianna (1990) and Laban (1978), which enable me, through your studies, think about building a personal technique for the dancing body. As a result, it is pointed out that the June bird is a cultural manifestation that contributes to the valorization of popular culture in Pará, as well as the creation process of the Pororoca character as an experience that reveals the subjectivity of the interpreter-creator as a power-place in creation of a character in dance and popular theater.